2001
DOI: 10.1590/s0100-39842001000500004
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento endovascular da oclusão das artérias ilíacas

Abstract: A oclusão das artérias ilíacas é uma patologia freqüente. Várias opções cirúrgicas existem para o seu tratamento, como a ponte aorto-bifemoral, a ponte femoro-femoral cruzada, o implante de endoprótese e outros. A ponte aorto-bifemoral é considerada o tratamento com melhores resultados. O tratamento endovascular da oclusão das artérias apresenta alta taxa de sucesso e baixo índice de complicações. Realizamos este tratamento em 24 pacientes, com idade média de 61 anos, variando de 39 a 82 anos. A indicação foi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
(3 reference statements)
1
3
0
Order By: Relevance
“…PTA associated with stent implantation is extremely effective in the treatment of iliac arterial stenosis of any etiology 14 . Patients usually have a good postoperative recovery, and clinical improvement is evident, as shown in this case and in the literature 12,14 .…”
supporting
confidence: 75%
See 2 more Smart Citations
“…PTA associated with stent implantation is extremely effective in the treatment of iliac arterial stenosis of any etiology 14 . Patients usually have a good postoperative recovery, and clinical improvement is evident, as shown in this case and in the literature 12,14 .…”
supporting
confidence: 75%
“…Therefore, in the arterial involvement of the lower extremities, varying degrees of arterial insufficiency may occur, from exertion muscular ischemia (intermittent claudication) to rest pain and tissue loss 12 …”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…1% 13 . Pedron et al 14 studied a series of 24 cases of iliac occlusion treated with angioplasty and found technical success rates of 91.7% and patency of 71% at 1 year 14 . Moreira et al 15 evaluated neointimal hyperplasia using intravascular ultrasound 8 months after the procedure in 30 patients that underwent angioplasty of the iliac arteries and stenting, and found that it was self-limited and did not lead to significant restenosis in any of the cases 15 .…”
Section: Discussionmentioning
confidence: 99%